Application of Tridax Procumbens on Cotton and Linen Fabric for Wound Healing - Kathiresan, T.; Thilagaraj, M. P.; Gopalakrishnan, M. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Various finishes were applied in the cotton and linen fabric. Here we use tridax procumbens herb extract for treatment on fabric. This study is mainly about wound healing medical fabric. For wound healing we choose tridax procumbens plant. The plants were collected from our college campus and dried and grained as a fine powder. Using soxhlet apparatus the ethanolic herbal extracts were taken and citric acid was added as a crosslinking agent. The extracts were treated on both cotton and linen fabric using normal dyeing method. The treated fabrics were subjected to an antimicrobial test to check the wound healing effect on the fabric. The treated samples should act against both gram positive and gram negative bacteria and check which has more efficiency on wound healing.